História e Natureza: mudanças ambientais no norte de Goiás em relatos de cronistas e viajantes naturalistas no século XIX - Santana, Raimundo Nonato Ribeiro (2014)
The nineteenth century was marked by numerous visits by naturalists travelers to Brazil. I highlight here Auguste François César Provençal Saint-Hilaire, Johann Emmanuel Pohl, George Gardner and Francis Castelnau, who visited with his expeditions Province of Goiás The reports of these travelers are documents that allow us to understand the transformation of the landscape over the centuries and regional history and Geography. The methodology used was: reading texts on the history and historiography of Nature; Reading the accounts of European travelers of the nineteenth century naturalists concerning the Province of Goiás, thus seeking to understand the changing landscape and the navigation of the Araguaia in travel accounts.